AKTIVITAS PENGHAMBATAN ENZIM TIROSINASE EKSTRAK METANOL KLIKA ANAK DARA (Croton oblongus Burm F.) - Afrisusnawati Rauf; Surya Ningsi; Andi Hasriani; Mukhriani Mukhriani (Jurnal Kesehatan, 2020)
Anak dara plant (Croton oblongus Burm. F) has been used by the people of Sinjai, South Sulawesi for generations as traditional cosmetics. Several studies have proven that this plant has antioxidant activity and sunscreen activity. Tyrosinase inhibitors are used in cosmetics to prevent hyperpigmentation. Inhibitory activity of the enzyme tyrosinease Anak dara tree bark (Croton oblongus Burm. F) has never been reported. This study aims to find out the inhibitory activity of tyrosinease enzyme of methanol extract Anak dara tree bark (Croton oblongus Burm. F). The extraction method used is maceration. Testing was carried out with L-tyrosine as a substrate, a methanol extract of Anak dara tree bark (Croton oblongus Burm. F) with concentrations of 20 ppm, 40 ppm, 60 ppm, 80 ppm, and 100 ppm, and Cojic acid as a positive control and then measured absorption using a micro plate reader at a wavelength of 490 nm. The results showed that the extract of methanol Anak dara tree bark (Croton oblongus Burm. F) has strong inhibitory activity of tyrosinase enzyme with an IC50 value of 76.80 μg/mL.